Differences in Depression, Anxiety, and Stress in Relation to Changes in Living Conditions, Work Conditions, and Daily Life During the COVID-19 Pandemic in Jordan - Abeer Shaheen; Khaldoun Hamdan; Rabia Allari; Ahmad M. Al-Bashaireh; Amani Al Smadi; Huda Amre; Maha Alkaid Albqoor (SAGE Publishing, 2024)
Introduction The COVID-19 pandemic was associated with numerous changes in daily life conditions that could affect the psychological response of individuals worldwide. Objective The study aimed to describe and examine differences in depression, anxiety, and stress in relation to living conditions during the COVID-19 pandemic. Methods A cross-sectional design was used. Purposive snowball sampling was employed to include 642 participants. Arabic versions of the Depression, Anxiety, and Stress Scales were used to collect data. Descriptive statistics, t-test, ANOVA, and Pearson's correlation were used to analyze the data. Results The total mean scores of depression, anxiety, and stress were 12.26 (SD = 10.53), 9.04 (SD = 9.34), and 13.49 (SD = 10.72), respectively. Of the study sample, 122 (19.5%), 139 (22.2%), and 99 (15.9%) had severe to extremely severe levels of depression, anxiety, and stress, respectively. Significant differences were found in depression, anxiety, and stress in relation to age, chronic diseases, and house size. Conclusion The findings showed an increased prevalence of depression and anxiety during the COVID-19 pandemic. Mental health practitioners need to recognize the impact of pandemics on youth, females, low-income populations, and individuals with chronic diseases. Preventive mental health services among these populations, such as screening and counseling, would help reduce the health risks.